2023
DOI: 10.14740/gr1623
|View full text |Cite
|
Sign up to set email alerts
|

Independent Predictors and Causes of Thirty-Day Gastrointestinal Readmissions Following COVID-19-Related Hospitalizations: Analysis of the National Readmission Database

Robert Kwei-Nsoro,
Bashar Attar,
Hafeez Shaka
et al.

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic led to significant mortality and morbidity in the United States. The burden of COVID-19 was not limited to the respiratory tract alone but had significant extrapulmonary manifestations. We decided to examine the causes, predictors, and outcomes of gastrointestinal (GI)-related causes of 30-day readmission following index COVID-19 hospitalization. Methods We used the National Readmission Database (NRD) from 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…According to available data, a study has shown that around 0.5% of individuals diagnosed with COVID‐19 have readmission within 30 days due to primary gastrointestinal reasons. The leading factors contributing to these readmissions are gastrointestinal bleeding, intestinal obstruction, acute diverticulitis, acute pancreatitis (AP), and acute cholecystitis 7 . The gut microbiota is crucial in maintaining human health since it is intricately linked to energy metabolism and immunological control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to available data, a study has shown that around 0.5% of individuals diagnosed with COVID‐19 have readmission within 30 days due to primary gastrointestinal reasons. The leading factors contributing to these readmissions are gastrointestinal bleeding, intestinal obstruction, acute diverticulitis, acute pancreatitis (AP), and acute cholecystitis 7 . The gut microbiota is crucial in maintaining human health since it is intricately linked to energy metabolism and immunological control.…”
Section: Introductionmentioning
confidence: 99%
“…The leading factors contributing to these readmissions are gastrointestinal bleeding, intestinal obstruction, acute diverticulitis, acute pancreatitis (AP), and acute cholecystitis. 7 The gut microbiota is crucial in maintaining human health since it is intricately linked to energy metabolism and immunological control. The gut microbiota is a critical intermediary for transmitting intestinal illnesses to extraintestinal organs.…”
mentioning
confidence: 99%